Acute Myeloid Leukemia (AML): The Role of Maintenance Chemo¬therapy - Thomas Büchner; Wolfgang Hiddemann; Wolfgang E. Berdel; Bernhard Wörmann; Helmut Löffler; Claudia Schoch; Torsten Haferlach; Wolf-Dieter Ludwig; Georg Maschmeyer; Eva Lengelder; Peter Staib; Reinhard Andreesen; et al. (International Journal of Hematology-Oncology and Stem Cell Research, 2004)
Maintenance treatment for patients with acute myeloid leukemia (AML) in remission has recently been controversially discussed and even abandoned by several groups. An analysis of 16 published multicenter trials, however, revealed the highest probabilities of relapse free survival (RFS) in the range of 35-42 % at 4-5 years only in patients assigned to maintenance treatment when adult age and intent-to-treat conditions were considered. After having demonstrated a superior RFS from 3 year maintenance following standard dose consolidation over that from consolidation alone (p<0.0001), the German AMLCG requestioned the effect of maintenance randomly compared with sequential high-dose AraC and Mitoxantrone (S-HAM) in patients having received intensified induction treatment. The RFS shows an advantage for maintenance with 32 % versus 25 % (p= .021). We conclude that maintenance treatment continues to substantially contribute to the management of adult patients with AML, even as part of recent strategies using intensified induction treatment, and thus appears necessary in these settings.